MEMBANGUN TRADISI QUR’ANI SEJAK USIA BELIA MELALUI PENGUATAN BACA TULIS AL-QUR’AN BERBASIS KOMUNITAS - Rahman; Lianti Novianti; Safiullah Drajat (Yayasan Baitul Hikmah al-Zain, 2025)
Quranic literacy is an essential aspect in strengthening the religious literacy of Muslims. Unfortunately, a number of communities in rural and marginalized areas still face limitations in accessing systematic and sustainable Quranic education. This article examines the implementation of a community service program designed to improve Quranic literacy through a community-based coaching approach. Implementation methods included intensive training, coaching local Quranic teachers, the use of structured modules, and a continuous monitoring and evaluation system. The program results showed significant improvements in the ability to recognize the hijaiyah letters, the makharijul huruf, and the skills to copy holy verses. Furthermore, the program encouraged the creation of a conducive, inclusive, and sustainable Quranic learning environment. The article concludes that the program's success was influenced by a participatory approach, multi-stakeholder collaboration, and adaptation of teaching methods to local characteristics.